Pakistan’s Political Development's Correlation with National Social Conditions: Measurement and Analysis - Taimoor Zeb Khan; Musavir Hameed; Attaullah Jan; Fahad Khan, (ASIAN Journal of International Peace & Security (AJIPS), 2022)
Political history of Pakistan reflects the least concern to political development because Pakistan has had centralized and authoritarian state structure since 1947. The process of democratization had been a wishful rhetoric of ruling elite until 2008 because the military regime had either abrogated or suspended the constitution three times and ruled the country for more than 30 years in its 75 years of history. Economy due to mechanisms of administration never set to position from where ray of hope could emerge. Institutions worked intermingled, and the system of independent operations were manipulated for personal favors every time. In this situation education sector in Pakistan also suffered. At the start, there were not enough and standardized educational institutions to produce and groom skilled citizens and to prepare them for modern competitive standards that would promote political development of the country. This research paper focuses on three main variables that are democratization, economy and education which have been used as an Index of Political Development and their co-relations with the social conditions which includes the military involvement, terrorism, and under-development respectively.